Nanotechnology-Enhanced Pharmacotherapy for Intervertebral Disc Degeneration Treatment - Shi S; Ou X; Liu C; Li R; Zheng Q; Hu L (International Journal of Nanomedicine, 2024)
Shaoyan Shi, Xuehai Ou, Chao Liu, Rui Li, Qianjin Zheng, Leiming Hu Department of Hand Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an Honghui Hospital North District, Xi’an, Shaanxi, 710000, People’s Republic of ChinaCorrespondence: Leiming Hu, Department of Hand Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an Honghui Hospital North District, Xi’an, Shaanxi, 710000, People’s Republic of China, Email huleiming0506@163.comAbstract: Intervertebral disc degeneration (IDD) is a primary contributor to chronic back pain and disability globally, with current therapeutic approaches often proving inadequate due to the complex nature of its pathophysiology. This review assesses the potential of nanoparticle-driven pharmacotherapies to address the intricate challenges presented by IDD. We initially analyze the primary mechanisms driving IDD, with particular emphasis on mitochondrial dysfunction, oxidative stress, and the inflammatory microenvironment, all of which play pivotal roles in disc degeneration. Then, we evaluate the application of metal-phenolic and catalytic nanodots in targeting mitochondrial defects and alleviating oxidative stress within the degenerative disc environment. Additionally, multifunctional and stimuli-responsive nanoparticles are explored for their capacity to provide precise targeting and controlled therapeutic release, offering improved localization and sustained delivery. Finally, we outline future research directions and identify emerging trends in nanoparticle-based therapies, highlighting their potential to significantly advance IDD treatment by overcoming the limitations of conventional therapeutic modalities and enabling more effective, targeted management strategies.Keywords: nanotechnology, drug delivery, intervertebral disc degeneration, regeneration, therapy